A combined analytical‐experimental investigation of friction in cylinder liner inserts under mixed and boundary regimes of lubrication. (16th January 2017) - Gore, M.; Morris, N.; Rahmani, R.; Rahnejat, H.; King, P. D.; Howell‐Smith, S.
Abstract: It is necessary to develop an analytical solution in order to combine predictions with measured tribological parameters and fundamentally understand the mechanism of lubrication in a typical region of engine cycle, using tribometric studies. This paper deals with the development of such a representative approach. An analytical, rather than a numerical approach is expounded, as it is shown to suffice for the purpose of precise time‐efficient predictions, which conform well to the measurements. The effect of surface topography, material and operating conditions are ascertained for the representative case of top compression ring—cylinder liner contact at the top dead centre reversal in transition from the compression to power stroke. Stainless steel uncoated surface used as press fit cylinder liners for niche original equipment manufacturer applications are compared with those furnished with a Nickel‐Silicon Carbide wear‐resistant coating of choice in high performance motorsport. © 2017 The Authors Lubrication Science Published by John Wiley & Sons Ltd.